INVESTIGATION OF PERIODONTITIS PATIENTS AND COMPARISON WITH CONTROL GROUP - M.H. Satan; P. OuIia; M. Khoshreza; Z. Kadkhoda (Tehran University of Medical Sciences, 1998)
The bacterial population found in the gingival sulcus region in periodontitis consists of gram negative microorganisms; most of them are obligate anaerobes and capnophil, including Porphyromonas, Prevotella, Fusobaclenuin, Welinella, Actinobacillus actinomycetem comitans, Eiknella and Capnocytohaga. This study has been carried out to investigate anaerobic and capnophilic bacteria from 206 specimens of patients with periodontitis and 145 specimens of control group. Different bacteria isolated from total specimens were obtained as follows: Actinobacillus actinomycetem comitans (patients group 36.9%, control group 4.1 %), Capnocytophaga (47.9%), Eikenella corodens (34.5% , 10.3%), Porphyryromonas gingivaIis (35% , 11%), Prevotella intermedius25.7%, 6.7%) and Prevotella melaninogenicus (13.6% , 3.4%).